Case Report: Thoracic duct ligation for left-sided chylothorax after pneumonectomy with contralateral VATS procedure using indocyanine green fluorescence - Schiena, Chiara Anna; Pezzella, Mario; Faccioli, Eleonora; Rebusso, Alessandro; Comacchio, Giovanni; Silvestrin, Stefano; Battistel, Michele; Rosellini, Edoardo; Dell’Amore, Andrea; Rea, Federico; Nicotra, Samuele (Frontiers in Surgery, 2025)
IntroductionChylothorax is a rare but potentially life-threatening condition characterized by the accumulation of lymphatic fluid in the pleural cavity. It is typically managed with conservative treatments such as fasting and/or thoracic duct embolization via lymphography. However, when these approaches fail, surgical intervention, most commonly thoracic duct ligation (TDL), is often necessary. While the advent of video-assisted thoracoscopic surgery (VATS) has enabled minimal invasive approaches for thoracic duct ligation, intraoperative identification of the thoracic duct remains technically challenging.Case reportWe present the case of a 62-year-old man diagnosed with SMARCB1-deficient mediastinal sarcoma who underwent left pneumonectomy and subsequently developed a left-sided chylothorax on postoperative day 16. Initial management with conservative strategy first, including two lymphography procedures with attempted embolization, was unsuccessful. Consequently, we proceeded with thoracic duct ligation via right-sided VATS, employing indocyanine green (ICG) fluorescence to aid in the identification of the thoracic duct. Given the prior left pneumonectomy, a single-lumen endotracheal tube with a bronchial blocker was used to selectively exclude the right lower lobe during the procedure.ConclusionThis case highlights the use of ICG fluorescence in facilitating the identification and ligation of the thoracic duct in a patient with left-sided chylothorax following left pneumonectomy.